Is negative density‐dependent reproduction regulated by density‐induced stress in root voles? Two field experiments. Issue 5 (13th May 2022) - Shang, Guozhen; Du, Shouyang; Yang, Yanbin; Wu, Yan; Cao, Yifan; Bian, Jianghui
Abstract: Density dependence in reproduction plays an important role in stabilizing population dynamics via immediate negative feedback from population density to reproductive output. Although previous studies have shown that negative density‐dependent reproduction is associated with strong spacing behavior and social interaction between individuals, the proximal mechanism for generating negative density‐dependent reproduction remains unclear. In this study, we investigated the effects of density‐induced stress on reproduction in root voles. Enclosed founder populations were established by introducing 6 (low density) and 30 (high density) adults per sex into per enclosure (four enclosures per density in total) during the breeding season from April to July 2012 and from May to August 2015. Fecal corticosterone metabolite (FCM) levels, reproductive traits (recruitment rate and the proportion of reproductively active individuals), and founder population numbers were measured following repeated live trapping in both years. The number of founders was negatively associated with recruitment rates and the proportion of reproductively active individuals, displaying a negative density‐dependent reproduction. FCM level was positively associated with the number of founders. The number of founder females directly affected the proportion of reproductive females, and directly and indirectly through their FCM levels affected the recruitment rate; the effect of the number of male founders on the proportion of reproductive males was mediated by their FCM level. Our results showed that density‐induced stress negatively affected reproductive traits and that density‐induced stress is one ecological factor generating negative density‐dependent reproduction. Abstract : Negative density‐dependent reproduction plays an important role in stabilizing population dynamics via immediate negative feedback from population density to reproductive output. In this study, we tested the hypothesis that negative density‐dependent reproduction in voles may be due to the suppressive effects of density‐induced stress on reproduction. We conclude that density‐induced stress is one ecological factor generating negative density‐dependent reproduction effects in vole populations.